Tortilla Chips Berbahan Tepung Jagung Nikstamal Dan Tepung Ikan Layang Sebagai Snack Tinggi Gizi - Liputo, Siti Aisa; Saman, Widya Rahmawaty; Limonu, Marleni; Mooduto, Delin (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Stunting is a growth disorder caused by malnutrition, characterized by height that is not in line with age standards. This occurs due to inadequate nutrient intake during the growth period. The purpose of this study was to evaluate the effect of the combination of nikstamal corn flour and ikan layang flour on the nutritional value and organoleptic properties of tortilla chips. This study used a completely randomized design (CRD) with one factor that included four treatments: T0 (100% nikstamal corn flour), T1 (90% nikstamal corn flour and 10% ikan layang flour), T2 (80% nikstamal corn flour and 20% ikan layang flour), and T3 (70% nikstamal corn flour and 30% ikan layang flour), each treatment was repeated three times. Parameters analyzed included moisture content, protein, fat, ash, carbohydrate, and organoleptic test. Data were analyzed using ANOVA, and if significant differences were found (P<0.05), DMRT (Duncan Multiple Range Test) was conducted. The results showed that moisture, protein, and fat content were significantly affected, while ash and carbohydrate content showed no significant effect. In terms of organoleptic, color, aroma, and taste were significantly affected, but texture was not. The best treatment based on the De Garmo method was T1, with fat content of 12.33%, carbohydrate 73.43%, protein 8.67%, water 4.28%, neutral aroma 4.44, neutral taste 4.52, neutral texture 4.56, slightly preferred color 5.08, ash content 1.29%, and calcium 31.73 mg/100g.